Predictor of abnormal gallbladder ejection fraction in patients with atypical biliary pain: Histopathological point of view. Issue 51 (December 2017) - Lim, Jun Uk; Joo, Kwang Ro; Won, Kyu Yeoun; Lim, Sung-Jig; Joo, Sun-Hyung; Yang, You-Jung
Abstract : Abstract: Cholescintigraphy has traditionally been used as a tool to select patients with biliary pain for elective cholecystectomy. However, atypical biliary pain presents a clinical challenge and there is no literature evaluating the factors of the gallbladder (GB) wall related to abnormal ejection fraction of cholescintigraphy in such patients. Therefore, we aimed to evaluate characteristics of the GB wall in patients with abnormal gallbladder ejection fraction (GBEF) on cholescintigraphy and atypical biliary pain. Patients who underwent cholescintigraphy for atypical biliary pain and subsequent cholecystectomy were initially recruited for this study. Medical records and pathologic findings of these patients were retrospectively reviewed. Parameters that were significant on univariate analysis, including factors of GB wall and cholescintigraphy, were subsequently tested by multivariate analysis to identify independent predictors for abnormal GBEF. Abnormal or low GBEF was defined as GBEF <35%. A total of 41 adult patients were divided into a low GBEF (n = 15) and a high GBEF group (n = 26) based on the cutoff value of 35%. In univariate analysis mean muscle thickness, muscle to total layer ratio, and muscle to fibrosis layer ratio were significantly higher in the low GBEF group than in the high GBEF group. In multivariate analysis, the muscle to fibrosis layer ratio was found to be an independent risk factor for abnormal GBEF (odds ratio = 3.514, 95% confidence interval = 1.058–11.673, P  = .04). The fibrosis to total layer ratio was negatively correlated with GBEF in the low GBEF group ( r  = −0.657, P  < .01). Muscle to fibrosis layer ratio was significantly associated with decreased GBEF. The fibrosis thickness ratio also seems to play an important role in patients with decreased GBEF.